Current problems and prospects of application of products based on continuous basalt fiber - Gigineishvili, J.; Gigineishvili, D.; Chikvaidze, G.; Savenko, V. (Ways to Improve Construction Efficiency, 2021)
The progress of science and technology significantly depends on the success in creating new materials. Composite materials are a heterogeneous structure formed by a combination of reinforcing elements and isotropic binder (binder) material, currently widely used in various fields of technology. but for the economy is more important mass application. For this purpose, more thorough and long-term research and experimental implementations are carried out, which require significant intellectual and material costs. Development of structural elements using basalt fiber began in NDIBV since 1987. and experimental samples of prestressed concrete structures with basalt-plastic reinforcement. Research to identify the interaction of cement with basalt fiber and the design of effective concrete structures using basalt reinforcement. Concrete beams with basalt reinforcement were successfully tested. Unfortunately, the results of research have not been widely implemented. Therefore, this article is devoted to the problems of mass introduction into construction practice of various types of composite materials, including basalt reinforcement. The advantages and disadvantages of composite reinforcement in comparison with steel are discussed. During the theoretical and experimental studies, both positive and negative aspects of the use of basalt reinforcement were identified. So experiments have shown that basalt fiber loses strength in the environment of Portland cement stone. But this shortcoming has been overcome by the efforts of scientists, it is important to use certain defects of basalt fibers for specific conditions. There are the following main types of basalt fibers: 1) basalt continuous fibers with a diameter of 8 - 11 microns, 12 - 14 microns, 16 - 20 microns with a fiber length of 25 - 50 mm and more; 2) staple short fibers with a diameter of 6 - 12 microns and a length of 5 - 10 mm and several diameters; 3) basalt superthin fibers with a diameter of 0.5 - 1 microns with a length of 10 - 50 mm; 4) coarse basalt fibers with a diameter of 100 - 400 microns. To create structures with certain properties for specific conditions, appropriate basalt fibers are selected. According to the research results, recommendations and normative documents have been developed. Suggestions for measures to improve and successfully widely use composite elements for reinforcement of concrete structures.